The Prevalence of Ocular Allergy and Comorbidities in Chinese School Children in Shanghai - Feng, Yanqing (Biomed Res Int, 2017)
OBJECTIVE: To investigate the prevalence and features of ocular allergy (OA) and comorbidities among school children in Shanghai, China. METHODS: This was a population-based cross-sectional study. Each participant completed an ISAAC-based questionnaire. The prevalence of OA symptoms, allergic rhinitis (AR) asthma, atopic dermatitis (AD), and sensitization to mites, pollen, and food was analyzed. RESULTS: A total of 724 and 942 completed questionnaires from the 7–9-year-old (young group) and the 12–14-year-old (teen group) groups were analyzed, respectively. The overall prevalence of OA symptoms was 28%. However, more young students (10.6%) reported mild to severe daily life interference caused by OA than the teens (5.7%). The young group had higher prevalence of diagnosed allergic conjunctivitis (10.2%). The overall prevalence of AR symptom, diagnosed asthma, and diagnosed AD was 40.4%, 11.6%, and 16.7%, respectively. Young children had higher prevalence of diagnosed AR and AD than the teens. There were gender associated differences in the prevalence of AR and asthma among young children, but not among the teens. The comorbidities associated with OA was also analyzed. Sensitization to mites, food, and pollen was associated with higher prevalence of allergic conditions. CONCLUSIONS: OA together with other allergic conditions affected a significant number of children in Shanghai.